A Novel Blind Deconvolution Method with Adaptive Period Estimation Technique and Its Application to Fault Feature Enhancement of Bearing. (27th November 2021) - Zhou, Qiuyang; Yi, Cai; Huang, Chenguang; Lin, Jianhui
Abstract : Minimum correlated generalized Lp / Lq deconvolution (MCG- Lp / Lq -D) is an important tool to detect periodic impulses in vibration mixture. It is proved to be a more stable technique than maximum correlated kurtosis deconvolution (MCKD) to recover the fault impulse under strong noise conditions. However, MCG- Lp / Lq -D still has limitations. One of the necessary conditions for the success of MCG- Lp / Lq -D is to provide a precise period of fault. An imprecise prior period will lead to performance degradation or even failure of the method. Therefore, in this paper, a MCG- Lp / Lq -D with adaptive fault period estimation capability is proposed, adaptive minimum correlated generalized Lp / Lq deconvolution (AMCG- Lp / Lq -D). The proposed method uses the autocorrelation function of envelope signal to estimate the fault period adaptively in each iteration and then takes the estimated period as the input parameter of MCG- Lp / Lq -D for the next iteration optimization. The proposed method does not require precise prior fault period input, which greatly improves the fault recovery accuracy and application range of MCG- Lp / Lq -D. Eventually, simulated and experimental data verify the effectiveness and superiority of AMCG- Lp / Lq -D.